Atrial Resection without Cardiopulmonary Bypass for Lung Cancer - Galetta, Domenico; Spaggiari, Lorenzo (The Thoracic and Cardiovascular Surgeon, 2019)
Background Results of resection of lung cancer invading left atrium (T4atrium) without cardiopulmonary bypass (CPB) remain controversial. We reviewed our experience analyzing surgical results and postoperative outcomes.Methods Patients who underwent extended lung resection for T4atrium without CPB between 1998 and 2018 were retrospectively reviewed using a prospective database.Results The study included 44 patients (34 males and 10 females; median age: 63 years). Twenty-five patients underwent preoperative mediastinal staging and 27 received induction treatment (IT). Surgery included 40 (90.9%) pneumonectomies, 3 (6.8%) lobectomies, and 1 bilobectomy (2.3%). Pathological nodal status was N0 in 10 patients (22.7%), N1 in 18 (40.9%), and N2 in 16 (36.4%). Four patients receiving IT had a complete pathological response (9.1%). Eight (18.2%) patients had microscopic tumor evidence on atrial resected margins. Mortality was nil. The major complication rate was 11.4%, including one bronchopleural fistula, one cardiac herniation, and three hemothoraces, all requiring reintervention. The minor complication rate was 25.5%. After a median survival of 37 months (range: 1–144 months), 20 (45.4%) patients were alive. Five-year survival rate and disease-free interval were 39 and 45.8%, respectively. Patients with N0 and R0 disease had a best prognosis (log-rank test: p = 0.03 and p = 0.01, respectively). IT neither influenced survival nor postoperative complications. On multivariate analysis, pN0 (p = 0.04 [95% confidence interval [CI]: 0.65–9.66] and negative atrial margins (p = 0.02 [95% CI: 0.96–8.35]) were positive independent prognostic factors.Conclusions T4atrium is technically feasible without mortality and acceptable morbidity. Patients with N2 cancers should not be operated. T4atrium should not be systematically considered as a definitive contraindication to surgery.
Keywords: lung cancer; cardiopulmonary bypass; CPB; cardiac